A polymorphic variant inside the osteopontin gene shows association with disease course in oligoarticular juvenile idiopathic arthritis. Issue 5 (8th September 2005) - Marciano, R; Giacopelli, F; Divizia, M T; Gattorno, M; Felici, E; Pistorio, A; Martini, A; Ravazzolo, R; Picco, P
Abstract : Background: Oligoarticular onset juvenile idiopathic arthritis (JIA) has a variable disease course. In some patients the disease remains confined to a few joints (persistent oligoarticular) while in others it extends to affect more joints (oligoarticular extended). Osteopontin is thought to play a role in the pathogenesis. Objective: To investigate whether a polymorphic variant in the human osteopontin gene, which is in linkage disequilibrium with recently characterised promoter variants, is associated with the disease course in oligoarticular JIA. Methods: Genotyping of the two base pair insertion/deletion variant at +245 in the first intron was undertaken by polymerase chain reaction (PCR) amplification of DNA fragments, using a fluorescently labelled primer, followed by allele detection after rapid separation of PCR products on an automated DNA sequencer. Results: Allele 2 of the polymorphic variant in the osteopontin first intron was significantly associated with the persistent oligoarticular form rather than the extended form of JIA. This was verified at the level of genotype and allele frequencies. Conclusions: The results suggest that osteopontin gene polymorphism is associated with the disease course in oligoarticular JIA and might therefore represent a useful genetic marker to characterise patients with oligoarticular JIA who are at risk of a worse outcome.